A comparative case study of the elements and principles of visual merchandising in three selected female teen apparel retail stores - Arriola, Melissa Therese D.; Mayo, Adelaida Villaraza (2005.)
The research aimed to analyze the application of the elements and principles of visual merchandising in three selected female teen apparel retail stores located in Robinson's Metro East Mall, but outside the department store area. The stores were limited to female teen apparel stores that were approximately the same size and in close proximity to each other. For ethical reasons the stores were referred to as Store A, Store B and Store C. The research was constrained within the time frame, the early summer months of 2005, it was being conducted to determine the current approach that was being used. The objectives of the study were to identify the principles and elements of visual merchandising applied in the store interiors, to compare and contrast the application of the principle and elements of store design among the three stores, to determine the approach in visual merchandising among the three stores, and to determine merchandising principles that will aid in designing stores. Purposive or judgmental sampling was used in choosing the three stores. The selection criteria included the following: stores were in close proximity to each other, their sizes were approximately the same, they had the same target market of females in their teens up to their late twenties, and they catered to the middle to upper income groups. Observation was the primary instrument used to conduct the study. Observation sheets were filled out accordingly and photo documentations were made to support the data. Similarities and differences in the application of the principles and elements of visual merchandising were noted and analyzed as well as the approaches that were being used at the time. The results were tabulated and analyzed according to the different principles and elements namely, finishes, color, display fixtures, light, space, line, balance, rhythm, emphasis and approach. Results showed that Store A presented an unconventional output of its interiors to go with the merchandise. Though the design was consistent with what was being sold, like the feminine and dainty interiors of Store C that complemented the feminine clothing that was being sold inside the store, it was overwhelming throughout its use of finish, color and display fixtures. The lighting was found to be dim and the space was very cramped. On the other hand Store B's interior was found to be clean and fresh, reflecting mostly the merchandise being sold for the summer months. Its interior was bright and spacious, with the area properly illuminated but was found to be very warm. The wall merchandise system was used beyond their capacity as well. Store C was very consistent in the portrayal of femininity with the white and pink finish and curving elements along with the merchandise being sold. It can be concluded that all three stores used a mainstream approach. In visual merchandising, the principles and elements of visual merchandising were applied but with varying degrees of skill in implementation. The stores are advised to practice moderation in displaying the merchandise since quality is better than quantity. Periodic evaluation of the stores is recommended as well since store merchandise and displays change every fashion season, such as spring, summer, and holiday seasons.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Display of merchandise; Stores, Retail